Twenty Years of Radiobiology in Clinical Practice: The Italian Contribution. Issue 6 (November 2014) - Strigari, Lidia; Caivano, Rocchina; Avanzo, Michele; Cremonesi, Marta; Arrichiello, Cecilia; Bianchi, Carla; Botta, Francesca; Califano, Giorgia; Ciscognetti, Nunzia; D'Alessio, Daniela; D'Ambrosio, Laura; D'Andrea, Marco; et al.
Aims and background: To present the Italian state-of-the-art contribution to radiobiology of external beam radiotherapy, brachytherapy, and radionuclide radiotherapy. Methods and study design: A survey of the literature was carried out, using PubMed, by some independent researchers of the Italian group of radiobiology. Each paper was reviewed by researchers of centers not comprising its authors. The survey was limited to papers in English published over the last 20 years, written by Italian investigators or in Italian institutions, excluding review articles. Results: A total of 135 papers have been published in journals with an impact factor, with an increase in the number of published papers over time, for external beam radiotherapy rather than radionuclide radiotherapy. The quantity and quality of the papers researched constitutes a proof of the enduring interest in clinical radiobiology among Italian investigators. Conclusions: The survey could be useful to individuate expert partners for an Italian network on clinical radiobiology, addressing future collaborative investigations.